Business process distribution: an intelligent approach. - Safi, Faramarz; Azmi Murad, Masrah Azrifah; Sulaiman, Md. Nasir; Udzir, Nur Izura (Asian Research Publishing Network (ARPN), 2008)
Business Processes in Service Oriented Architecture(SOA) are run using an orchestrate engine. The point here is that running a huge number of business processes under a centralized orchestrate engine result in degrading of run-time environment abilities. Apart from this, running clustered orchestrate engines as an alternative way to obviate centralized orchestrate engine problems is not a final solution. On the other hand, there exist many researches focusing on decomposing or segmentation of business processes in run-time some of which attempts to decompose a business process to its building activities, while others break business process parts to sub flows or segments. Decomposing of a business process to its building activities will lead to a large number of activity agents in run time and it subsequently leads to more resource consumption and run-time system degradation. Segmentation, though, is useful however there are no criteria for business process segmentation commensurate with run-time environment requirements. In this paper,we introduce an intelligent process distribution method to first) increase business process adaptability with run-time environment, second) choose the best granularity for segments as well as encapsulating them in agents and third) decrease resource consumption due to reduced number of agents and messages. We also prove the correctness of our method mathematically.